IMR 665: Management of Audio Visual Records & Archives. Individual Assignment: Article summary / Muhamad Fauzan Mohamad Fadzil - Mohamad Fadzil, Muhamad Fauzan (2015)
Article Summary: "Digital preservation of audio, video and film and The public-private partnership case study in digitization of audiovisual heritage”